Modelling Cyberspace to Determine Cybersecurity Training Requirements - Venables, Adrian (Frontiers in Education, 2021)
Cyberspace is a constantly evolving and expanding environment that is being used for an ever-increasing range of purposes. As such, it attracts numerous threat actors seeking to identify and exploit its vulnerabilities. In order to be able to fully mitigate the risk of compromise, it is necessary to first understand the nature and composition of cyberspace and how it is used. This chapter seeks to address this issue by presenting a method to model cyberspace in three dimensions with humans included as an integral part. Expanding beyond describing cyberspace purely in terms of technology and its uses, it explores geographic, political, and temporal aspects to reflect its dynamic nature. The first component of the model examines the varied attributes of cyberspace ranging from the landscape in which its components are located to how they are used. The second dimension investigates the path of data in all its forms from its source to destination, emphasising that cyberspace is fundamentally a communications medium and is not borderless. Thirdly it focuses on the security dimension and the motivations of those with malicious intent, demonstrating the multidisciplinary and essentially human nature of cybersecurity in countering their activities.